CTIM-24. NUTMEG: A RANDOMIZED PHASE II STUDY OF NIVOLUMAB AND TEMOZOLOMIDE VERSUS TEMOZOLOMIDE ALONE IN NEWLY DIAGNOSED ELDERLY PATIENTS WITH GLIOBLASTOMA. (14th November 2022) - Sim, Hao-Wen; Lwin, Zarnie; Barnes, Elizabeth; McDonald, Kerrie; Yip, Sonia; Verhaak, Roel; Heimberger, Amy; Hall, Merryn; Wong, Matthew; Jennens, Ross; Ashley, David; Rosenthal, Mark; et al.
Abstract: BACKGROUND: Nivolumab is a PD-1 inhibitor with known safety profile. An increase in mutations as we age is well documented in glioblastoma and other cancers. Higher mutational load is associated with increased response to nivolumab in extracranial malignancies. NUTMEG examined the activity of nivolumab added to temozolomide in glioblastoma patients aged ≥ 65 years. METHODS: NUTMEG was an international multicenter phase II trial for newly diagnosed glioblastoma patients aged ≥ 65 years, randomized 2:1 to experimental (40Gy/15 fractions with temozolomide 75mg/m 2, then 6 cycles of temozolomide 150-200mg/m 2 D1-5 Q28D + nivolumab 240mg D1, 15 Q28D C1-4 and 480mg D1 Q28D C5-6) versus standard arm (40Gy/15 fractions with temozolomide 75mg/m 2, then 6 cycles of temozolomide alone 150-200mg/m2 D1-5 Q28D), stratified by age, ECOG status, MGMT status and resection extent. RESULTS: 103 patients were enrolled (69 in experimental arm, 34 in standard arm). Median age was 73 years, 36% ECOG 0, 57% MGMT -unmethylated and 51% gross macroscopic resection. Median follow-up is 31 months to date, with 77 deaths (surviving patients to continue follow-up and final results will be presented). Median overall survival was 11.8 months in the experimental arm versus 12.0 months in the standard arm (HR 0.95 95%CI 0.59-1.53 for experimental relative to control). Six-month progression-free survival rate using mRANO was 64% in the experimental arm versus 49% in the standard arm (HR 0.81 95%CI 0.51-1.26). Grade 3/4 adverse events were reported in 46% of experimental arm (7% lung infection, 7% thromboembolic events, 6% fatigue, 6% muscle weakness) and in 29% of control arm (9% fatigue, 6% seizure, 6% thromboembolic events). CONCLUSIONS: There was insufficient evidence of clinical benefit with nivolumab in this population. No new safety signals were identified. Central imaging review is underway and correlative studies will characterize the immune landscape, including mutational load, neoantigen and other immune markers. NCT04195139.